Effect of different weed management practices on growth and yield of spring rice (Oryza sativa L.) in Banke, Nepal - Bista, Samiksha; Bhatta, Sandesh; B.K., Kamal; Pandey, Nikita; Shreepaili, Briksha; Basnet, Bishesh (Journal of Agriculture and Natural Resources, 2023)
Rice (Oryza sativa L.) is the most important crop in Nepal, despite having significant contribution to food security and agricultural economy, its production is being affected greatly by weed infestation. A field experiment was conducted during the spring season of 2022 to evaluate the different weed management practices in transplanted spring rice at Radhapur, Banke, Nepal. Seven weed management treatments were laid in Randomized Complete Block Design (RCBD) with three replications. The treatments were pre-emergence application of Pendimethalin 50% EC, 1 kg a.i./ha, at 3 DAT, post-emergence application of Bispyribac Na 10% SC, 25 g a.i./ha, at 28 DAT, pre-emergence application of Pendimethalin followed by post-emergence Bispyribac Na, Pre-emergence application of Pendimethalin followed by one hand weeding at 40 DAT and Farmer’s practice i.e. one hand weeding at 40 DAT along with two controls (weedy free and weedy check). The rice variety Hardinath-1 was used in the experiment. Data regarding the weed flora, weed density, weed dry weight, rice growth, yield attributes and yield was recorded and analyzed. Weed flora in the experimental plot comprised of 11 weed species viz. five were broadleaf weeds belonging to four families, four grasses belonging to Poaceae family whereas three sedges belonging to Cyperaceae family. Sedges weeds were dominant as compared to broadleaf and grasses. The highest number of effective tillers per m2 (413) and number of grains per panicle (101.33) were obtained in Pendimethalin followed by Bispyribac Na treated plot. The plot treated with combination of pre-emergence followed by post emergence recorded significantly the lowest weed density (9.67 weeds/m2) at 60 DAT. This treatment significantly gave higher grain (4780 kg/ha), straw yield (4318 kg/ha) yield, harvest index (52.55%), other traits like sterility (22.19%) was recorded least and thousand grains weight was significantly higher (23.61g). The yield on weedy check plot produced the lowest yield as compared to weed free plot. Sedges weeds such as Cyperus difformis, Cyperus iria and Fimbristylismiliaceae were dominant as compared to dicots such as Amaranthus spinosus, Chenopodium album and grasses such as Echinochloa crus-galli, Echinochloa colonum at the experimental field. The ultimate overall analysis revealed that the application of pre-emergence followed by post-emergence herbicide was the best treatment so far as compared to other weed management treatments considering various data regarding variables.